Efektivitas Edukasi Media Video Animasi Terhadap Pengetahuan Anemia Pada Remaja Putri - Endang Lestiawati, Endang Lestiawati; Desti; Cristin Wiyani; Ririn Wahyu Widayati; Tia Amestiasih (IKES Payung Negeri Pekanbaru, 2025)
Introduction: World Health Organization (WHO) data in the WHO global anaemia estimates in 2025, shows that the prevalence of anemia in women of reproductive age (15-49) in the world in 2023 is around 30.7%. According to the 2023 Indonesian Health Survey (SKI) report, the prevalence of anemia among adolescent girls is 18%. Anemia in adolescent girls can cause disruptions in the menstrual cycle, which affects hormonal balance and adolescent reproductive health. One of the factors contributing to the increasing cases of anemia in adolescents is the lack of knowledge about the condition. One of the efforts to increase knowledge is through health education by using animated videos. The purpose of the study was to determine the effectiveness of animated videos on knowledge about anemia in adolescent girls at SMP Negeri 3 Ngaglik, Sleman. Method: Type of quantitative research quasi experimental method with pre and post test design without control. The number of samples was 58 respondents using purposive sampling technique. The intervention was in the form of education using animated videos about anemia. The data collection technique uses questionnaires and data analysis used by the Wilcoxon test. Results: the results of data analysis showed an increase in knowledge scores after being educated, with an average increase of 2.5 and a p-value of 0.003. Conclusion: animated videos have been shown to be effective in increasing knowledge about anemia in adolescent girls at SMP Negeri 3 Ngaglik, Sleman.